WORKPLACE STRESS AND BURNOUT AMONG EMPLOYEES IN HIGH-TECHNOLOGY AND RESEARCH INSTITUTIONS: A REVIEW OF NURSING ROLES AND INTERVENTIONS - Abdullahi Isah Kuba; Ajesha Musa Paul (Yassawi Journal of Health Sciences, 2026)
Stress and burnout have become significant issues in high-tech and research institutions, particularly for employees in demanding environments. This systematic review examines the causes, consequences, and nursing interventions for workplace stress and burnout. Utilizing peer-reviewed articles from PubMed, Scopus, and Google Scholar, with keywords like "workplace stress," "burnout," and "nursing interventions," the review highlights organizational, environmental, and psychological stressors as primary contributors to burnout. Nursing professionals play a crucial role in offering stress management interventions, including mindfulness-based stress reduction (MBSR), cognitive behavioral therapy (CBT), and peer support networks, which can alleviate emotional exhaustion and improve job satisfaction. The review also identifies barriers to the implementation of these interventions, such as organizational constraints, workforce adaptation challenges, and ethical considerations related to AI in nursing practice. Despite these challenges, the study emphasizes the importance of training nurses in AI, designing nursing-specific tools, and fostering organizational support to reduce stress and burnout. Recommendations for improving nursing interventions and enhancing overall well-being in high-tech and research settings are provided.